Data privacy and security in health information management: Challenges for nursing and pharmacy professionals - Alyamani, Abdullah Mohammed Abdullah; Alsulami, Ahmad Nafal Mohmmed; Raea, Salem Mohammad; Alruqaie, Reef Ibrahim Mohammed; Albather, Mohammed Hassan; Alamri, Badr Jaza; Alharb, Majed Ayidh; Alshareef, Wafa Abdullah; Binselm, ‏Khalid Rashad; Alshaghroud, ‏Salah Mohammed; Altwaijri, Saleh Abdullah; Alrashed, Mohammed Abdulrahman (International journal of health sciences, 2018)
Background: The integration of information and communication technologies in healthcare has revolutionized patient care globally. However, rural and remote areas face challenges in accessing essential healthcare services, including pharmacy care. Telepharmacy has emerged as a promising solution to bridge this gap and provide quality pharmaceutical services to underserved populations. Methods: This study reviews the concept of telepharmacy, focusing on its models, operational processes, and the role of pharmacists in delivering remote pharmacy services. It explores the use of technologies like videoconferencing and automated dispensing systems in telepharmacy setups, detailing how pharmacists interact with patients and healthcare providers in distant locations. Results: Telepharmacy models have shown significant success in improving medication access and patient outcomes in remote areas. Studies indicate that active pharmacist engagement in telepharmacy services reduces adverse drug events, enhances medication monitoring, and promotes medication compliance. The involvement of pharmacists in telepharmacy has led to cost savings, decreased medication errors, and improved medication documentation in regions lacking adequate pharmacy services. Conclusion: Telepharmacy emerges as a transformative approach to healthcare delivery, particularly in rural and remote regions with limited access to pharmacy services.